Bird by bird : some instructions on writing and life - Lamott, Anne. (New York : Anchor Books, 1995)
A step-by-step guide to writing and managing the writer's life covers each portion of a written project, addresses such concerns as writer's block and getting published, and offers awareness and survival tips.
Originally published: New York : Pantheon Books, 1994.
Keywords: Authorship -- Handbooks, manuals, etc